2008
DOI: 10.1177/039463200802100127
|View full text |Cite
|
Sign up to set email alerts
|

Parecoxib as an Alternative in COX-2 Hypersensitivity

Abstract: The group of non-steroidal anti-inflammatory drugs (NSAIDs) is commonly involved in hypersensitivity reactions. In clinical practice the physician is often faced with the need to choose an alternative anti-inflammatory agent for a patient who has suffered a hypersensitivity reaction to a NSAID. The most common approach to choosing the safest NSAID is to perform a challenge test. Parecoxib is the first injectable COX-2 selective inhibitor indicated for the treatment of acute postoperative pain. The authors repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
1
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…Findings also support the view that neuro-immune abnormalities occur in the brain of autistic patients and may contribute to the diversity of the autistic phenotypes (4). Although several lines of research support the view that this is a result of a complex combination of neurological, environmental, immunological, and genetic factors, it is widely reported that several white blood cells are important in the pathogenesis of neurological diseases (5)(6)(7)(8), and it is established in animal and human diseases such as autoimmunity, inflammation and cancer (9)(10)(11)(12)(13)(14). In addition, proinflammatory cytokines secreted by different types of cells contribute to the pathogenesis ofneuro-inflammation (12,15).…”
supporting
confidence: 63%
“…Findings also support the view that neuro-immune abnormalities occur in the brain of autistic patients and may contribute to the diversity of the autistic phenotypes (4). Although several lines of research support the view that this is a result of a complex combination of neurological, environmental, immunological, and genetic factors, it is widely reported that several white blood cells are important in the pathogenesis of neurological diseases (5)(6)(7)(8), and it is established in animal and human diseases such as autoimmunity, inflammation and cancer (9)(10)(11)(12)(13)(14). In addition, proinflammatory cytokines secreted by different types of cells contribute to the pathogenesis ofneuro-inflammation (12,15).…”
supporting
confidence: 63%
“…Substance P (SP) is a potent modulator of monocyte/macrophage function and causes transcription and translation of several different cytokines/chemokines such as tumor necrosis factoralpha (TNF-alpha), macrophage inflammatory protein-l (MIP-l) and GM-CSF, RANTES, MCp• 1, CXCL8, along with other proinflammatory compounds, proteases (chymase and tryptase), histamine, leukotrienes and prostaglandin 02 (6,(68)(69)(70).…”
mentioning
confidence: 99%